Beyond the Primary Influences of Parents and Peers on Very Young Adolescent Alcohol Use: Evidence of Independent Community Associations. (June 2014) - Smith, Dayna T.; Kelly, Adrian B.; Chan, Gary C. K.; Toumbourou, John W.; Patton, George C.; Williams, Joanne W.
This study examined the extent to which young adolescent alcohol use was related to alcohol-related norms and law enforcement of underage alcohol use, after accounting for known strong parent and peer correlates. Our sample consisted of 7, 674 students (X ¯ age = 12 years) from 30 Australian communities. Two-level (individuals nested within communities) binary logistic regression was used to examine relationships between recent alcohol use (last 30 days) and perceived community norms about alcohol use, perceived law enforcement of underage alcohol use, parent alcohol use, parent permissiveness of adolescent alcohol use, peer alcohol use, and demographic factors. Results indicated that community norms and perceived law enforcement of alcohol use were associated with alcohol use and this association was independent of parent and peer factors. After accounting for proximal social correlates, community factors were significantly associated with alcohol use among very young adolescents.